Kompetence prihodnosti v športni industriji - Širok, Klemen (Šport (Ljubljana), 2025)
The sport industry is undergoing rapid transformation driven by digitalisation, automation, and the spread of artificial intel-ligence. These shifts are reshaping workforce demands and raising questions about the adequacy of existing competency models. This article applies a foresight-oriented methodol-ogy, adapting international skills anticipation practices to the specificities of sport. The analysis relies primarily on grey lit-erature, including industry foresight reports and benchmarks findings against the European Skills, Competences, Qualifica-tions and Occupations (ESCO) framework and a recent sys-tematic review of sport management competencies. Results show strong convergence between established competen-cies—such as leadership, communication, adaptability, and ethical commitment—and emerging requirements for digital, data, and AI-related skills. At the same time, critical gaps are evident: cybersecurity, digital security, and advanced digital skills (e.g., immersive media, AI governance). These competen-cies are insufficiently reflected in current frameworks despite their growing importance. The study concludes that curricula and training pathways in sport must integrate both technical and human-centred competencies. Flexible formats such as micro-credentials can serve to strengthen the missing skills
Keywords: competencies; future skills; kompetence; napovedovanje kompetence; prihodnost; skill forecasting; sport industry; športna panoga; technological change; tehnološke spremembe; veščine; workforce development